Labor's view of quality of working life programs - Wurf, Jerry (Journal of business ethics, 1982)
The quality of working life and the quality of business ethics cannot be separated. In the private sector, the profit priority motivates most employer behavior, which can be characterized as mean and rationalistic. Management-initiated ‘quality of life’ programs are usually disguised attempts to achieve a speedup. From the union perspective, fair wages and working conditions are synonymous with the quality of working life, and unions pursue these through collective bargaining, which is essentially adversarial in both the public and private sectors. AFSCME's approach is to negotiate for better staffing, career ladders, and other workplace improvements that contribute to a worker's sense of dignity and satisfaction.